PENERAPAN MEDIASI PADA SAAT PANDEMI COVID-19 TERHADAP PENUNDAAN PEMBAYARAN HUTANG DI BPSK DKI JAKARTA - Salsabila Mutiara Puspa, (2022)
Disputes between consumers and business actors are, of course, unavoidable, especially during the Covid-19 pandemic which almost paralyzed the world economy. Mediation is one of the dispute resolution processes carried out by the Consumer Dispute Settlement Agency (hereinafter referred to as 'BPSK'), one of which is through BPSK DKI Jakarta Province. During the Covid-19 pandemic, many complaints were submitted to the DKI Jakarta BPSK regarding consumer problems affected by the Covid-19 pandemic and resulted in the affected consumers not being able to carry out their obligations to business actors. The purpose of this paper is to analyze the application of mediation during the Covid-19 pandemic to delaying debt payments based on the determination of number 050/PNTP/BPSK-DKI/IV/2021, and to find out the differences in the application of mediation before and during the Covid-19 pandemic at BPSK DKI Jakarta. This research method uses a normative juridical approach with a law and case approach and uses primary legal materials in the form of the Consumer Protection Act and related regulations. The results of the study show that the application of mediation during the Covid-19 pandemic at BPSK DKI Jakarta for delaying debt payments is one of the right solutions that can be taken for dispute resolution in the midst of difficult conditions such as the Covid-19 pandemic, because there is convenience from mediation carried out in BPSK DKI Jakarta. One of the disputes that was successfully resolved through mediation with the final determination of an agreed mediation issued by BPSK DKI Jakarta was BPSK Determination Number 050/PNTP/BPSK-DKI/IV/2021. Meanwhile, regarding the difference in the application of mediation before the Covid-19 Pandemic and after the Covid-19 Pandemic at BPSK DKI Jakarta, there were several changes related to the application of mediation carried out at BPSK DKI Jakarta.